Features of the Preparation of Consolidated Financial Statements - M. A., Abduganiyev (Research Parks Publishers, 2023)
In this article, the authors focus on the practical aspects of preparing consolidated financial statements based on international standards, which widely use induction and deduction, monographic observation, factor analysis, synthesis and other methods.